Case Study of Various Parameters by Applying Swing Up Control for Inverted Pendulum - Kunal Chakraborty; Amit Kumar Sen; Rahul Dev Basak; Rahul Raushan (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
This paper investigates behavior of the system in terms of time response e.g., steady state error, rise time & overshoot & then compare it with FLC. Being an unstable system, Inverted Pendulum is very common control problem being assigned to control its dynamics. It is almost impossible to balance a pendulum in the inverted position except applying some force from outside to the system.